La Moraine du Lac Bluenose (Territoires du Nord-Ouest), une moraine à noyau de glace de glacier - St-Onge, Denis A.; McMartin, Isabelle (Géographie physique et Quaternaire, 1999)
South of Dolphin and Union Strait, N.W.T., massive ridges of bouldery till, up to 100 m high, delimit an ice frontal position to the east and north of Bluenose Lake. Major ridges are either massive or composite with linear longitudinal pattern on their crest. Up ice (east from the ridges the most common landforms are boulder-covered hills, up to 60 m high, and hummocks interspersed with numerous lakes. In a well exposed section, sediment-rich ice is overlain by a bouldery till, more than 3 m thick, with a sandy to sandy silt matrix, columnar jointing and prismatic fissility. The icy sediments exhibit banding, folding and complex deformations, and include numerous boulders, cobbles, and pebbles. The upper contact of the icy sediments and the bouldery diamicton is sharp, subhorizontal and unconformable. These massive icy sediments are interpreted as basal glacier ice buried by the stacking of glacigenic debris, mostly till, carried at the base of a thrust-sheet in an area of compressive flow. This occurred in the ice frontal zone of an active Late Wisconsinan ice mass. It is postulated that if the regional climate was to warm to the point of melting the icy sediments which form the bulk of the Bluenose Lake Moraine the resulting landscape would be hummocky terrain similar to that which covers extensive regions in more southerly parts of Central Canada. Au sud du détroit du Dolphin et de l'Union, dans les Territoires du Nord-Ouest, des crêtes morainiques hautes de 100 m, composées de till à gros blocs marquent l'emplacement d'un front glaciaire à l'est et au nord du lac Bluenose. Les principales crêtes sont soit massives, soit composites avec de petites crêtes secondaires à leur sommet. En amont glaciaire (est) des crêtes, les formes de relief les plus fréquentes sont des collines recouvertes de blocs dont la hauteur atteint 60 m et des monticules entre lesquels se trouvent de nombreux lacs. Un important glissement de terrain au cœur de la moraine expose de la glace riche en sédiments, enfouie sous 3 m de till. ...